60.1k views
1 vote
Please Help It Is Past Due!

Prove the Pythagorean Theorem using similar triangles. The Pythagorean Theorem states that in a right triangle, the sum of the squares of the lengths of the legs of the triangle equals the squared length of the hypotenuse. Be sure to create and name the appropriate geometric figures.

1 Answer

5 votes

Step-by-step explanation:

First we consider ΔABC and ΔBCD,

∠C=∠C (common)

∠B=∠D=
90\textdegree

So, ΔABC ≈ ΔBCD (By AA similarity rule )

So by taking corresponding sides in ratios we get


(AB)/(BD)=(AC)/(BC)=(BC)/(CD)

Now


AC.CD=BC.BC\\BC^(2) =AC.CD -------- Eqn (1)

Similarly,

We consider ΔABD and ΔABC

∠A=∠A (Commom)

∠B=∠D=
90\textdegree

So,

ΔABD ≈ ΔABC (By AA similarity rule )

So by taking corresponding sides in ratios we get


(BC)/(BD)=(AC)/(AB)=(AB)/(AD)

Now,


AB.AB=AC.AD\\AB^(2) =AC.AD --------Eqn (2)

By Adding both the equation we get


AB^2+BC^2=AC.CD+AC.AD\\AB^2+BC^2=AC(CD+AD)\\AB^2+BC^2=AC.AC\\AB^2+BC^2=AC^2

Hence, we proved the pythagorean theorem by using similarity of triangle.



Please Help It Is Past Due! Prove the Pythagorean Theorem using similar triangles-example-1
User Tomas Hromnik
by
6.3k points